Fraud in Banking Financial Reports in Indonesia from an Agency Perspective (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the factors that cause fraud in financial reporting. The study analyzed 195 data points from 39 financial institutions listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023 using a purposive sampling technique. The research applied multiple linear regression analysis to analyze the impact of governance independence and performance variables on the likelihood of fraudulent financial reporting. The independent variables include financial targets assessed by profitability (return on assets [ROA]), financial stability measured by changes in assets, external pressure measured by the debt-to-equity ratio (DER), and the proportion of independent commissioners as a measure of good corporate governance. The study proves that financial targets affect fraudulent financial reporting, while financial stability, external pressure, and independent commissioners do not influence fraudulent financial reporting. The findings of this study provide valuable insights for regulators, investors, and management to enhance oversight and reduce the risk of fraud in the banking sector.